THE GENUS FIRMIANA MARSILI (Sterculiaceae) - A. J. G. H. KOSTERMANS (Reinwardtia, 1957)
1. Firmiana Marsili and Erythropsis Lindley are congeneric. 2. Firmiana Marsili links Sterculia L. and Scaphium Schott & Endl. 3. Eight species are recognized: Firmiana eolorata (Roxb.) R. Br.;F. diversifolia A. Gray; F. fidgens (Wall, ex King) Corner; F. hainanensis Kosterm.; F. major Hand.-Mazz.; F. papuana Mildbr.; F. philippinensis Kosterm.; F. simplex (L.) W. F. Wight. 4. Seventeen binomials are referred to other genera.